StkTokens: Enforcing well-bracketed control flow and stack encapsulation using linear capabilities. (15th April 2021) - SKORSTENGAARD, LAU; DEVRIESE, DOMINIQUE; BIRKEDAL, LARS
Abstract: We propose and study StkTokens: a new calling convention that provably enforces well-bracketed control flow and local state encapsulation on a capability machine. The calling convention is based on linear capabilities: a type of capabilities that are prevented from being duplicated by the hardware. In addition to designing and formalizing this new calling convention, we also contribute a new way to formalize and prove that it effectively enforces well-bracketed control flow and local state encapsulation using what we call a fully abstract overlay semantics.